Dilemmatic Intersection in Cryptococcal Meningitis Treatment: Side Effects, Drug Resistance, and Efficacy - Japutri, Josephine; Lalisang , Lilie; Sutanto, Anyeliria (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2025)
Background Fluconazole resistance in Cryptococcus neoformans is progressively increasing over the past 10 years, particularly in developing countries, which reached 43.6% resistance rate. This case demonstrates the emerging dilemma of cryptococcal meningitis management with antifungal resistance. Case Summary A 31-year-old male with HIV presented with severe headache, hearing loss, and fever. Brain imaging was within normal limits, and CSF analysis showed increased cell count (86, PMN 10, MN 76), elevated protein, glucose ratio <0.4, positive India ink, and positive Cryptococcus Ag, leading to a diagnosis of cryptococcal meningitis. He was treated with IV Amphotericin B for 14 days and Fluconazole, but developed acute kidney injury (AKI), delaying further fluconazole therapy. One month later, he returned with severe headache; CSF re-analysis showed positive Cryptococcus culture and fluconazole resistance. The patient was treated again with IV Amphotericin B for 14 days. Discussion Azole resistance in Cryptococcus spp is associated with ERG11 gene mutation which is the fluconazole’s target. Interruption of fluconazole in cryptococcal meningitis during the theraphy phase could be the risk factor for acquired resistance. The minimum inhibitory concentrations (MIC) test can help in the selection of therapy with Cryptococcus breakpoint for fluconazole susceptibility is MIC < 8 μg/mL. In previous cases, itraconazole and voriconazole were proven to replace fluconazole. However, in this case, there were limitations in costs and treatment coverage. Conclusion Drug evaluation in parallel with treatment in Cryptococcal meningitis, with prior fluconazole use or delayed therapy, is recommended. Keywords: Cryptococcal Meningitis, HIV, Fluconazole resistance